Cross-sectional analysis of risk factors associated with Mugil cephalus in retail fish markets concerning methicillin-resistant Staphylococcus aureus and Aeromonas hydrophila - Attia, Amira S. A.; Abou Elez, Rasha M. M.; El-Gazzar, Nashwa; Elnahriry, Shimaa S.; Alfifi, Ahmed; Al-Harthi, Helal F.; Alkhalifah, Dalal Hussien M.; Hozzein, Wael N.; Diab, Hassan Mohmoud; Ibrahim, Doaa (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Aeromonas hydrophila and methicillin-resistant Staphylococcus aureus (MRSA) are potent bacterial pathogens posing major hazards to human health via consuming fish harboring these pathogens or by cross-contamination beyond the contaminated environment. The aim of this study was to determine risk variables associated with the presence of certain pathogenic bacteria from Mugil cephalus fish in retail markets in Egypt. The virulence genes of A. hydrophila and S. aureus were also studied. Furthermore, the antibiotic sensitivity and multidrug resistance of the microorganisms were evaluated. Methods In a cross-sectional investigation, 370 samples were collected from mullet skin and muscle samples, washing water, fish handlers, knives, and chopping boards. Furthermore, fish handlers’ public health implications were assessed via their response to a descriptive questionnaire. Results S. aureus and Aeromonas species dominated the investigated samples with percentages of 26.76% and 30.81%, respectively. Furthermore, A. hydrophila and MRSA were the predominant recovered bacterial pathogens among washing water and knives (53.85% and 46.66%, respectively). The virulence markers aerA and hlyA were found in 90.7% and 46.5% of A. hydrophila isolates, respectively. Moreover, the virulence genes nuc and mec were prevalent in 80% and 60% of S. aureus isolates, respectively. Antimicrobial susceptibility results revealed that all A. hydrophila isolates were resistant to amoxicillin and all MRSA isolates were resistant to amoxicillin and ampicillin. Remarkably, multiple drug resistance (MDR) patterns were detected in high proportions in A. hydrophila (88.37%) and MRSA (100%) isolates. The prevalence of Aeromonas spp. and S. aureus had a positive significant correlation with the frequency of handwashing and use of sanitizer in cleaning of instruments. MRSA showed the highest significant prevalence rate in the oldest age category. Conclusion The pathogenic bacteria recovered in this study were virulent and had a significant correlation with risk factors associated with improper fish handling. Furthermore, a high frequency of MDR was detected in these pathogenic bacteria, posing a significant risk to food safety and public health.